Flash Eurobarometer 366 (Quality of Life in European Cities) - European Commission, Brussels DG Communication COMM A1 ´Research and Speechwriting´ (2017)
Quality of life in European cities. Topics: satisfaction with the following facilities and issues in the own city: public transport, health care services, sports facilities, cultural facilities, state of streets and buildings, public spaces, green spaces, availability of retail shops, schools and other education facilities, quality of air, noise level, cleanliness; approval of selected statements about the own city: satisfied to live there, easy to find a job, positive influence of foreigners on the city, good integration of foreigners, easy to find good housing at a reasonable price, efficient administrative services, feeling of safety in the city and in the neighbourhood, commitment to fight climate change, trustworthiness of inhabitants, people in the neighbourhood, and public administration; satisfaction with: personal job situation, financial situation of the own household, personal life, place of residence; most important issues for the own city. Demography: city; age; sex; nationality; household composition and household size; marital status; duration of living in the own city; financial difficulties during the last year; age at end of education; occupation; professional position; type of community; own a mobile phone and fixed (landline) phone. Additionally coded was: respondent ID; weighting factor. Lebensqualität in europäischen Großstädten. Themen: Zufriedenheit mit den folgenden Einrichtungen und Gegebenheiten am Wohnort: öffentlicher Nahverkehr, Gesundheitsversorgung, Sportanlagen, kulturelle Einrichtungen, Zustand von Straßen und Gebäuden, öffentliche Flächen, Grünflächen, Vorhandensein von Geschäften, Schulen und andere Bildungseinrichtungen, Luftqualität, Lärmbelastung, Sauberkeit; Zustimmung zu ausgewählten Aussagen zum Wohnort: zufrieden, dort zu leben, Arbeitsstelle ist leicht zu finden, Anwesenheit von Ausländern ist gut für die Stadt, Ausländer sind gut integriert, gute Wohnungen zu bezahlbaren Preisen, effiziente Behörden, Gefühl von Sicherheit in der Stadt und in der eigenen ...